Mxd1 mediates hypoxia‐induced cisplatin resistance in osteosarcoma cells by repression of the PTEN tumor suppressor gene. Issue 10 (15th June 2017) - Zheng, Datong; Wu, Weiling; Dong, Na; Jiang, Xiuqin; Xu, Jinjin; Zhan, Xi; Zhang, Zhengdong; Hu, Zhenzhen
Abstract : Hypoxia‐induced chemoresistance remains a major obstacle to treating osteosarcoma effectively. Mxd1, a member of the Myc/Max/Mxd family, was shown to be involved in the development of drug resistance under hypoxia. However, the effect of Mxd1 on hypoxia‐induced cisplatin (CDDP) resistance and its mechanism in osteosarcoma have not been fully elucidated. In this study, we demonstrated that HIF‐1α‐induced Mxd1 contributed to CDDP resistance in hypoxic U‐2OS and MG‐63 cells. The knockdown of Mxd1 expression elevated PTEN expression at both protein and RNA levels in these hypoxic cells. Using Luciferase reporter and ChIP assays, we confirmed that Mxd1 directly bound to the E‐box sites within the PTEN promoter region. We further demonstrated that PTEN knockdown decreased CDDP sensitivity in Mxd1 siRNA‐transfected U‐2OS and MG‐63 cells under hypoxia. Our results also showed that Mxd1 deficiency in hypoxic U‐2OS and MG‐63 cells lead to inactivation of PI3K/AKT signaling, which is the downstream of PTEN. Furthermore, blockade of PI3K/AKT signal re‐sensitized hypoxic U‐2OS and MG‐63 cells to CDDP. Taken together, these findings suggest that HIF‐1α‐induced Mxd1 up‐regulation suppresses the expression of PTEN under hypoxia, which leads to the activation of PI3K/AKT antiapoptotic and survival pathway. As a result CDDP resistance in osteosarcoma cells is induced.